Research of Control Strategy for High-voltage Suspended Type Reactive Power and Harmonic Integrative Compensator - 罗仁俊; 张定华; 王卫安; 黄超; 黄燕艳; 曹洋; 刘华东; 唐建宇 (Kongzhi Yu Xinxi Jishu)
In order to solve the problem that reactive power and harmonic are compensated separately in high and medium voltage grid, a new high voltage suspended compensator constituted by static var generator based on H-bridge cascade and LC in parallel. The utilization and compensative range of active capability are improved by combining a low cost LC. A reactive power, individual harmonic and negative sequence detection method and controlling arithmetic based on digital band pass filter and multiple synchronous rotating coordinates are proposed, thus the real-time detection and compensative control are realized. For the questions of DC voltage balancing control of cascaded SVG, a new control technique of phase angle superposition is described. The topology structure and compensative principle are analyzed and the comprehensive compensative control and DC balancing control are also addressed. The whole control strategy is verified by simulation and experiment, and the results show that this method can achieve compositive compensation effect, DC voltage balancing and stabilization and good dynamic performance.